OPTIMIZATION OF WASTE MANAGEMENT TO REDUCE GHG OF SOUTH TANGERANG CITY - LYDI FERABIANIE NIM: 25314750, AYU
Waste increasing in the landfill has the potential to degrade the quality of the environment globally. Waste management activities can produce different GHG emissions, waste collection methods can lead to methane gas, while waste management with incinerators also contribute emissions of CH4 and N2O. Waste management through the transfer depo, waste bank and composting can reduce GHG emissions. Generation of waste generated in South Tangerang City with a population of 1,6 million people amounted to 2.453,99 tons/day. With that amount of waste it will produce a high GHG if not followed by optimum waste management. Based on that, this study aims to calculate the amount of GHG emissions generated based on waste management targets contained in the master plan document of integrated waste management system in South Tangerang City and create a model with dynamic system approach to produce a combination of waste management of South Tangerang City. The emission calculation of waste generation data that has been obtained is done by Intergovernmental Panel on Climate Change (IPCC) approach. GHG emissions are determined based on four waste management and transportation scenarios. The results obtained using the template developed by IPCC 2006 for GHG emissions in 2045 scenario 1 of 344.292 tons CO2eq, scenario 2 of GHG emissions reached 316.743 tons CO2eq, and for scenario 3 GHG emissions obtained by 390.346 tons CO2eq. The simulation result using dynamic system, the percentage of waste reduction for scenario 1 is 0,56%, scenario 2 is 0,79%, scenario 3 is 1,02% and the scenario jakstra is 2,13%. Total GHG emission scenario 1 is 19.077.841 ton CO2eq, scenario 2 is 18.417.375 ton CO2eq, scenario 3 is 12.386.228 ton CO2eq and scenario jakstra is 9.795.686 ton CO2eq. The lowest total cost is in scenario 1 which is Rp. 280 billion/ year, then scenario 2 total cost is Rp. 294 billion/year, scenario 3 total cost is Rp. 325 billion/ year and the largest total cost is scenario jakstra Rp. 328 billion/year